RACIAL PROFILING IN ANGIE THOMAS’ THE HATE U GIVE - Wella Clarisa (STBA Prayoga Padang, 2020)
ABSTRACT It still becomes the issue that racial profiling is still done by the White police to Black young people in the United States. For that condition, Black people struggle to put racial profiling to an end. The struggle is reflected in one of Angie Thomas’ work, The Hate U Give, which shows the incident of racial profiling experienced by the main Black characters, Starr and her best friend, Khalil. In discussing the issue, the writer used the theory of Orientalism from Edward W. Said. The concepts used to answer research questions are Occident, Orient, and Power. The qualitative descriptive method was applied to analyze the incident of racial profiling by finding relevant quotations that contain evidence and racism. The writer found Prejudice, Stereotype, and Racial Discrimination as the causes of racialprofiling in many cases. Black people do racial socialization and the Black Lives Matter Movement to oppose racial profiling.